Penggunaan Alat Bukti Tidak Langsung Oleh Komisi Pengawas Persaingan Usaha Dalam Perkara Kartel Di Indonesia; Studi Putusan Nomor 294k/pdt.sus/2012 dan 163/pdt.g/kppu/2017 - Dwi Anggorowati; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThe use of Indirect Evidence in Business Competition Law, especially in handling cases becomes a problem in its own right for the judiciary, both for the KPPU institution, as well as the District Court and the Supreme Court as the highest institution in the judiciary, because there are pros and there are also contra to the use of Indirect evidence. This study uses a normative legal research method using the law approach and case approach. The legislative approach refers to Law Number 5 of 1999 and its implementing regulations, namely the Regulation of the Business Competition Supervisory Commission Number 4 of 2010 concerning Cartels, while for the case approach based on the Decisions of the Business Competition Supervisory Commission, District Courts and Supreme Court with the aim of exploring and understand the meaning of different truths in cases that have been decided by the Supreme Court against the Decision of the Business Competition Supervisory Commission which has permanent legal force. The results of this study reveal that the power of proof using Indirect Evidence still reaps the pros and cons, where in the use of Indirect Evidence in each case the strength of the evidence is different.Keywords:Indirect evidence, Cartel, KPPU, Supreme Court